Two-step degradation of a-InGaZnO thin film transistors under DC bias stress. (February 2019) - Hu, Chun-Feng; Teng, Tong; Qu, Xin-Ping
Highlights: A unified explanation is proposed to consistently explain the two-step degradation of a-IGZO TFTs under DC PBTI stress without or with different stress Vds . For PBTI stress without stress Vds, the initial negative Vth shift is believed to be induced by donor-like defect states corresponding to H2 O molecule and intrinsic defects. For PBTI stress with stress Vds, the negative shift is believed to be induced by donor-like defect states corresponding to oxygen vacancies. The gate-bias-induced electron trapping mechanism is responsible for the positive Vth shift. Abstract: A unified explanation is proposed to consistently explain the two-step degradation of amorphous InGaZnO (a-IGZO) thin film transistors (TFTs) under DC positive bias temperature instability (PBTI) stress without or with different drain stress voltages ( Vds ). For PBTI stress without stress Vds, this initial negative Vth shift is believed to be induced by donor-like defect states corresponding to H2 O molecule and intrinsic defects, while for PBTI stress with stress Vds, the negative shift is believed to be induced by donor-like defect states corresponding to oxygen vacancies. The gate-bias-induced electron trapping mechanism is responsible for positive Vth shift. These transitions from negative to positive Vth shift are resulted from the competition between the donor-like states creation and electron trapping.